Establishing Journalistic Standards for the Publication of Negative Results. (May 2018) - Kittelman, Angus; Gion, Cody; Horner, Robert H.; Levin, Joel R.; Kratochwill, Thomas R.
We argue in this article that there are conditions in which publication of negative results can make a useful contribution. Three small-scale examinations of journal publication criteria for publishing negative results were conducted. We first reviewed 29 journals from education and school/counseling psychology to assess author submission guidelines for reporting negative results. We then reviewed the most recent issue of each of the 29 journals to determine whether articles reporting negative results were being published. Finally, we surveyed the editors of the 29 journals to examine conditions in which they perceived it appropriate to publish articles that did not demonstrate experimental effects. Results of these studies indicate that currently only one of the 29 journals provides formal guidance to authors about submitting papers with negative results. Two articles published in the 29 journals in their last issue of 2016 contained only negative results. And, of the 60% of the editors who responded to our survey, 96% indicated there were conditions in which publication of negative results was appropriate. In conclusion, we propose situations in which studies reporting negative results would make a valuable contribution.